2022
DOI: 10.3389/fphar.2022.944376
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical reserpine models recapitulating motor and non-motor features of Parkinson’s disease: Roles of epigenetic upregulation of alpha-synuclein and autophagy impairment

Abstract: Reserpine is an effective drug for the clinical treatment of hypertension. It also induces Parkinson’s disease (PD)-like symptoms in humans and animals possible through the inhibition of monoamine vesicular transporters, thus decreasing the levels of monoamine neurotransmitters in the brain. However, the precise mechanisms remain unclear. Herein, we aimed to develop a preclinical reserpine model recapitulating the non-motor and motor symptoms of PD and investigate the underlying potential cellular mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have discovered a downregulation of autophagic components, including Lc3, Beclin-1, p62 and ATG5, in peripheral blood cells of patients with Pd (46,47). Abnormal expression of these autophagy-related proteins in the SN of Pd-related mice is accompanied by both upregulated α-synuclein and clinical symptoms, such as constipation, olfactory impairment and depression-like behaviors (48). Therefore, these findings indicate that autophagy is involved in the pathological process of Pd.…”
Section: Effects Of Autophagy In Pdmentioning
confidence: 91%
“…Recent studies have discovered a downregulation of autophagic components, including Lc3, Beclin-1, p62 and ATG5, in peripheral blood cells of patients with Pd (46,47). Abnormal expression of these autophagy-related proteins in the SN of Pd-related mice is accompanied by both upregulated α-synuclein and clinical symptoms, such as constipation, olfactory impairment and depression-like behaviors (48). Therefore, these findings indicate that autophagy is involved in the pathological process of Pd.…”
Section: Effects Of Autophagy In Pdmentioning
confidence: 91%
“…The repeated administration of a low dose of reserpine results in a progressive appearance of motor symptoms in rats which supports the use of reserpine to induce PD animal models (Fernandes et al 2012;Li et al 2022). These motor impairments are accompanied by an enhanced oxidative stress which has been implicated as a possible pathophysiological mechanism in PD (Gaki and Papavassiliou 2014;de Farias et al 2016].…”
Section: Discussionmentioning
confidence: 65%
“…Recently, Li et al ( 2022 ) demonstrated that reserpine induced motor and non-motor symptoms similar to PD. The authors found that reserpine caused alpha- synuclein deposition, autophagy impairment and tyrosine hydroxylase reduction in the substantia nigra and proposed reserpine model as a valuable tool in PD studies.…”
Section: Introductionmentioning
confidence: 99%
“…All data are presented as the mean ± SEM. Data from pramipexole and reserpine treatment in the FST analysis (supplementary data) are the same batch analyzed in our recent study [39]. Differences between two groups were determined with an unpaired twotailed Student's t test.…”
Section: Discussionmentioning
confidence: 99%